Analisis Pemicu Ketegangan Antara Kaum Mutafaqqih Terhadap Kaum Sufi Tentang Fiqih Dan Agama - Hosen Hosen (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2023)
One of the problems that occur in Islamic civilization is the conflict and debate among Muslims. This is because there is a difference in perception between the Sufis whose views are spiritual in nature and the mutafaqqih who are external in nature. However, the difference in principle between the two mutafaqqih and the Sufis is only at an empirical level. Due to the fact that fiqh is symbolic, legalistic, exoteric and formalistic in nature so that it tends to see an action from conditions and pillars, legal and illegal. This research will only examine the differences in the views of the mutafaqqih towards the Sufis in matters of jurisprudence and religion from a historical perspective. This research concludes that among the reasons for the disagreement between the Sufis and the mutafaqqih regarding fiqh and religion is the existence of a disagreement between the two. The difference is in the outer and inner aspects, if the mutafaqqih focus on practicing the shari'ah, while the Sufis focus on the inner side so that they continue to remember Allah SWT and feel pleasure with him. Since the beginning of history, Sufism has not tolerated Sufis and their teachings. The mutafaqqih accuse the Sufis of rejecting formal worship or ritual aspects of Islam, while the mutafaqqih accuse the Sufis of only dealing with inner development, so they are accused of ignoring the outward laws of the Shari'a. Keywords: Mutafaqqih, Sufi, Fiqh, Religion